2017
DOI: 10.1016/s2352-3026(17)30088-1
|View full text |Cite
|
Sign up to set email alerts
|

Janus kinase-2 inhibitor fedratinib in patients with myelofibrosis previously treated with ruxolitinib (JAKARTA-2): a single-arm, open-label, non-randomised, phase 2, multicentre study

Abstract: Sanofi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
199
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(203 citation statements)
references
References 20 publications
2
199
0
2
Order By: Relevance
“…13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib. 21 Here, we report the outcome of 218 patients after ruxolitinib.…”
Section: Introductionmentioning
confidence: 99%
“…13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib. 21 Here, we report the outcome of 218 patients after ruxolitinib.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Fedratinib has been FDA approved for intermediate‐2 and high‐risk myelofibrosis, but its clinical development had been prematurely discontinued due to a full clinical hold, placed in 2013, and lifted in 2017. FDA hold was placed when accrual of JAKARTA‐2 had just been completed, so that patients received a median of six cycles of treatment while on trial, while the median duration of fedratinib exposures in JAKARTA were 28 to 30 weeks …”
Section: Resultsmentioning
confidence: 99%
“…FDA hold was placed when accrual of JAKARTA-2 had just been completed, so that patients received a median of six cycles of treatment while on trial, while the median duration of fedratinib exposures in JAKARTA were 28 to 30 weeks. 82,83 Moreover, many patients treated with JAK inhibitors were pretreated with hydroxyurea or with alkylating agents; thus, the risk of LPN could be the result of a cumulative phenomenon of immunosuppression and dysregulated immunological surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…As illustration, fedratinib, a JAK2 inhibitor, was previously shown to be superior to placebo for control of splenomegaly and symptoms in patients with MF in the Jakarta 1 and 2 studies. 70 Further development of fedratinib was discontinued in November 2013 due to concerns of Wernicke's encephalopathy (WE) observed in 8 of the 877 total patients treated with fedratinib. However, a reanalysis in late 2017 suggested that only one of these eight patients met the diagnostic criteria for WE, and the drug is now being redeveloped.…”
Section: Sm In the Midostaurin Eramentioning
confidence: 99%
“…The majority of other Type 1 JAK2 inhibitors have had their clinical development discontinued largely due to the emergence of serious neurotoxicity. As illustration, fedratinib, a JAK2 inhibitor, was previously shown to be superior to placebo for control of splenomegaly and symptoms in patients with MF in the Jakarta 1 and 2 studies . Further development of fedratinib was discontinued in November 2013 due to concerns of Wernicke's encephalopathy (WE) observed in 8 of the 877 total patients treated with fedratinib.…”
Section: Introductionmentioning
confidence: 99%